2020
DOI: 10.1002/agj2.20458
|View full text |Cite
|
Sign up to set email alerts
|

Response of nitrogen redistribution to irrigation at jointing in winter wheat

Abstract: To explore the effect of irrigation at the jointing stage on nitrogen (N) redistribution after flowering and productivity effects of water and N in winter wheat (Triticum aestivum L.), a 2‐yr field experiment was conducted between 2015 and 2017. Three irrigation regimes were designed as follows: rain‐fed (W0), irrigation at jointing and 7 d after flowering (W1), and irrigation at 7 d after flowering (W2). Compared with W2, W1 increased spike number, kernels per spike, and N and dry matter (DM) accumulation at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 50 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…Moreover, there is a negative association between GPC and total irrigation amount ( Moradi et al., 2022 ). Wu et al. (2020) also found that the concentration of grain protein was significantly increased by a water deficit during the grain-filling stage.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Moreover, there is a negative association between GPC and total irrigation amount ( Moradi et al., 2022 ). Wu et al. (2020) also found that the concentration of grain protein was significantly increased by a water deficit during the grain-filling stage.…”
Section: Discussionmentioning
confidence: 75%
“…In this regard, the findings of some studies (Beral et al, 2020;Sanchez-Bragado et al, 2020) have indicated that the TGW is negatively correlated with grain number. Wu et al (2020) also found that irrigation at the jointing stage increased spike number, kernels per spike, and grain yield, but reduced grain weight. Consistently, we detected a significant negative relationship between TGW and the NGB (r = -0.58, p< 0.05) in the present study.…”
Section: Effects Of Drought Stress On the Yield And The Mechanisms Wh...mentioning
confidence: 80%
See 1 more Smart Citation
“…We found that, compared with irrigation of other border lengths, L40 treatment promoted significantly higher grain nitrogen accumulation by increasing the grain nitrogen accumulation rates (Vmax and Vmean; Figure 7, Table 3). The low rate of nitrogen accumulation in grains under L20 and L30 treatments may be due to low nitrogen transport in vegetative organs, and to water stress, resulting in premature leaf senescence and reduced nitrogen accumulation in plants after anthesis [12]. Compared with that under L40 treatment, the decrease in the grain nitrogen accumulation under L50 treatment was mainly due to excessive irrigation, which caused the plants to retain nitrogen in stems and leaves and mature late; high temperatures in the later growth stage led to their rapid maturity, and the nitrogen accumulation in the stems and leaves was not transferred to the grains [39].…”
Section: Discussionmentioning
confidence: 99%
“…However, water stress significantly reduces the absorption of nitrogen by plants, and insufficient nitrogen reduces the chlorophyll content in leaves and the accumulation of photosynthetic products [11]. In another study, the plant nitrogen accumulation at anthesis, net photosynthetic rate in flag leaves after anthesis, and grain yield under supplemental irrigation at jointing and anthesis were 45.8%, 24%, and 8.86% higher, respectively, than those under supplemental irrigation at anthesis only [12]. Many studies of the effect of soil moisture and irrigation period on plant nitrogen accumulation have been conducted; however, information on the characteristics of grain nitrogen accumulation and the activity of nitrogen metabolic enzymes in flag leaves, especially under irrigation with different border lengths, is limited.…”
Section: Introductionmentioning
confidence: 96%